Glucosinolates and myrosinase activity under different conditions in papaya (Carica Papaya) - Loumi © Noumie Surugau; Ivy Wong Nyet Kui; Annie Johanna Ahmad (Universiti Malaysia Sabah, 2012)
Glucosinolatesu ndergo hydrolysis readily upon cell rupture (such as cutting and heating) by the naturally-occurring enzyme myrosinase to form mainly isothiocyanates and/or nitriles. Isothiocyanates are known to possess anticarcinogenicp roperties while nitriles are largely inactive. Benzyli sothiocyanate (BITC), a hydrolysis product of benzyl glucosinolate (BGSL), is one of the most potent anticancer agents. Papaya (Carica papaya) is known to contain has high amount of BITC. The first objective of this study is to profile BGSL in different parts of papaya namely seeds, leaf and unripe fruit pulp and the second objective is to study enzymolysisa nd myrosinasea ctivity under different conditions. Ther esults showed that seed has the highest content (in mg/100g dry weight) of BGSL (i. e. 490 f 14.14) compared to leaf (14.7 f 3.56) and unripe fruit pulp (12.5 f 0.71). The optimum conditions for the activitiy of crude myrosinase extract from the different papaya parts are as follows: hydrolysis time, seed at 20 minutes (99.16%), leaf at 60 minutes (100 %) and unripe fruit pulp at 30 minutes (83.30%) ; temperature, 30 - 40'C (all parts); pH, 8 (seed), 7 (leaf), 9 (unripe fruit pulp); concentration of ascorbic acid, 2.0 mM (all parts); no effect for all the iron concentrations tested. The findings show that myrosinase activity can occur in optimally in mild temperature within a short time and in neutral condition. As for the additives, higher concentration of ascorbic acid inhibit the activity while presence of iron does not affect myrosinase activity. Overall, this work shows that papaya seed is a rich source of BGSL, the precursor for the anticancer BITC. To ensure optimum uptake of BITC, food preparation methods must be performed in optimum conditionsf or the endogenousm yrosinaset o take place.